2016
DOI: 10.1111/apt.13845
|View full text |Cite
|
Sign up to set email alerts
|

The Endoscopic Reference Score shows modest accuracy to predict either clinical or histological activity in adult patients with eosinophilic oesophagitis

Abstract: Summary Background Conflicting results have been recently reported for the accuracy of the Endoscopic Reference Score (EREFS), an standardised endoscopic classification, to predict the histological activity of eosinophilic oesophagitis (EoE). Aim To evaluate the accuracy of the EREFS to predict either histological or clinical activity of EoE. Methods Prospective multicentre study conducted in eight Spanish centres evaluating adult EoE patients, either naïve or after treatment. Symptoms were evaluated before up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 32 publications
(100 reference statements)
1
30
0
2
Order By: Relevance
“…5,6,13 Dellon et al 4 assessed an EREFS inflammatory score, derived by adding the maximum score for edema, exudate, and furrows. We found this score well correlated with eosinophilia in all areas of the esophagus (proximal, mid, and distal), and ROC analysis showed the score accurately distinguished incident EoE from control, and post-treatment active from inactive disease.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,13 Dellon et al 4 assessed an EREFS inflammatory score, derived by adding the maximum score for edema, exudate, and furrows. We found this score well correlated with eosinophilia in all areas of the esophagus (proximal, mid, and distal), and ROC analysis showed the score accurately distinguished incident EoE from control, and post-treatment active from inactive disease.…”
Section: Discussionmentioning
confidence: 99%
“…34 Other studies have shown weak to modest association between EREFS score and histology findings. 35,36 This discrepancy might be related, in part, to the variable resolution of endoscopic findings with medical therapy, depending on whether the resolution occurs via reductions in inflammation or fibrosis. Endoscopic findings (and symptoms) might also be an important marker of disease activity, regardless of biopsy eosinophil count.…”
Section: Endoscopymentioning
confidence: 99%
“…Since EREFS represents a tool to standardize and classify the endoscopic features according to a more IF or FS dominant subtype of EoE [9,25] with good inter-and intra-observer reliability, we correlated EREFS with EoE subtypes. Our findings that the FS type presents with significantly higher EREFS suggest that EoE presents with a variety of mixed endoscopic signs, and a co-existence of IF and fibrotic endoscopic abnormalities [9,25,26] is more often seen than a strictly defined EoE subtype.…”
Section: Discussionmentioning
confidence: 66%
“…In our study, we found no support for this thesis, as the FS EoE subtype did not correlate with the severity of dysphagia. No single endoscopic feature was significantly associated with the degree of dysphagia; a positive trend toward patients' reported dysphagia was seen for exudates, fixed rings, and crêpe paper mucosa [26] . Our findings question whether the use of a non-validated dysphagia score is adequate to evaluate and grade symptoms in EoE patients.…”
Section: Discussionmentioning
confidence: 90%